Perancangan Interior Shinjuku Hairmake di Surabaya - Adi Santosa, Irene Yovita Yusuf (Intra, 2014)
Interior Design Shinjuku Hairmake Surabaya is a project of designing the interior of a place of beauty and hair care that located in the city of Surabaya. interior design can attract the curiosity and provide comfort for visitors. Facility that will be designed are the lobby, waiting room, haircut hall, hairwash room, hair care hall, makeup hall, nail art hall, retail hall, and staff hall. This design is expected to provide the characteristics and identity of the Shinjuku Hairmake in Surabaya. With an attractive interior and comfortably space can be a plus point for the salon itself, supported with lighting and regular circulation